HUBUNGAN KEMANDIRIAN BELAJAR DALAM MASA PANDEMI COVID 19 TERHADAP PRESTASI BELAJAR FISIKA SISWA KELAS XI IPA TAHUN AJARAN 2020/2021 - ANDRIONO MANALU; MUKTAR PANJAITAN (JURNAL ILMIAH MAKSITEK, 2020)
This study is an attempt to determine a positive and significant relationship and to determine the value contribution oflearning independence during the Cocid 19 pandemic to the physics learning achievement of class XI IPA students in the2020/2021 academic year. This type of research is a correlational research with the research subjects are students of classXI IPA 2 SMA Negeri 5 Pematangsiantar, totaling 35 students. The instruments used in this study were the independentlearning questionnaire and the students' physics achievement test using multiple choice forms that had been tested forinstrument validation. Based on the results of data analysis, it was obtained that the Fcount value was 0.875> the F tablevalue was 2.46 and the correlation coefficient r count was 0.504> rcount was 0.334. Then H_0 was rejected and H_a wasaccepted. This means that there is a relationship between independent learning on student achievement in physics class XIIPA SMA Negeri 5 Pematangsiantar with a coefficient of determination of 0.254, which indicates that 25.4% of students'physics learning achievement is influenced by independent learning while the remaining 74.6% is influenced. by othervariables not examined in this study. So that the results of the data analysis indicate that there is a positive and significantrelationship between independent learning and students' physics learning achievement.